(untitled) (Academicia Globe: Inderscience Research, 2021)
One of the main pests of spider mites is air temperature 7.30C. emerges from the winter and multiplies in weeds. It comes down to cotton from the fourth generation. Vertimek energy 1.8% g / l 0.4 l / ha, Abama 36 3.6% g / l 0.3 l / ha, Agrilex 5% g / l 0.2 l / ha were used against this pest and Agrilex 5% g / l 0.2 l / hectare The drug achieved high biological efficiency. 26.8 ts / ha in our control variant, the average yield in our variant using Vertimek energy is 1.8% g / l, 31.9 ts / ha in control, 5.1 ts / ha% g / l in our variant o The average yield is 32.2 ts / ha, 5.4 ts / ha more than the control, Agrilex in our variant is 5% g / l, the average yield is 34.5 ts / ha. We can see this to be 7.7 ts / ha more than the control.